The first chemically-synthesised, highly immunogenic anti-SARS-CoV 2 peptides in DNA genotyped aotus monkeys for human use (2021)
ABSTRACT: Thirty-five peptides selected from functionally-relevant SARS-CoV-2 spike (S), membrane (M), and envelope (E) proteins were suitably modified for immunising MHC class II (MHCII) DNA-genotyped Aotus monkeys and matched with HLA-DRb1* molecules for use in humans. This was aimed at producing the first minimal subunit-based, chemically synthesised, immunogenic molecules (COLSARSPROT) covering several HLA alleles. They were predicted to cover 48.25% of the world’s population for 6 weeks (short-term) and 33.65% for 15 weeks (long-lasting) as they induced very high immunofluorescent antibody (IFA) and ELISA titres against S, M and E parental native peptides, SARS-CoV-2 neutralising antibodies and host cell infection. The same immunological methods that led to identifying new peptides for inclusion in the COLSARSPROT mixture were used for antigenicity studies. Peptides were analysed with serum samples from patients suffering mild or severe SARS-CoV-2 infection, thereby increasing chemically-synthesised peptides’ potential coverage for the world populations up to 62.9%. These peptides’ 3D structural analysis (by 1 H-NMR acquired at 600 to 900 MHz) suggested structural functional immunological association. This first multi-protein, multi-epitope, minimal subunit-based, chemically-synthesised, highly immunogenic peptide mixture highlights such chemical synthesis methodology’s potential for rapidly obtaining very pure, highly reproducible, stable, cheap, easily-modifiable peptides for inducing immune protection against COVID-19, covering a substantial percentage of the human population.